If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(2X + -3) = (x + 2)(4x + -5) Reorder the terms: (1 + 2x)(2X + -3) = (x + 2)(4x + -5) Reorder the terms: (1 + 2x)(-3 + 2X) = (x + 2)(4x + -5) Multiply (1 + 2x) * (-3 + 2X) (1(-3 + 2X) + 2x * (-3 + 2X)) = (x + 2)(4x + -5) ((-3 * 1 + 2X * 1) + 2x * (-3 + 2X)) = (x + 2)(4x + -5) ((-3 + 2X) + 2x * (-3 + 2X)) = (x + 2)(4x + -5) (-3 + 2X + (-3 * 2x + 2X * 2x)) = (x + 2)(4x + -5) (-3 + 2X + (-6x + 4xX)) = (x + 2)(4x + -5) (-3 + 2X + -6x + 4xX) = (x + 2)(4x + -5) Reorder the terms: -3 + 2X + -6x + 4xX = (2 + x)(4x + -5) Reorder the terms: -3 + 2X + -6x + 4xX = (2 + x)(-5 + 4x) Multiply (2 + x) * (-5 + 4x) -3 + 2X + -6x + 4xX = (2(-5 + 4x) + x(-5 + 4x)) -3 + 2X + -6x + 4xX = ((-5 * 2 + 4x * 2) + x(-5 + 4x)) -3 + 2X + -6x + 4xX = ((-10 + 8x) + x(-5 + 4x)) -3 + 2X + -6x + 4xX = (-10 + 8x + (-5 * x + 4x * x)) -3 + 2X + -6x + 4xX = (-10 + 8x + (-5x + 4x2)) Combine like terms: 8x + -5x = 3x -3 + 2X + -6x + 4xX = (-10 + 3x + 4x2) Solving -3 + 2X + -6x + 4xX = -10 + 3x + 4x2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 2X + -6x + 3 + 4xX = -10 + 3x + 3 + 4x2 Reorder the terms: -3 + 3 + 2X + -6x + 4xX = -10 + 3x + 3 + 4x2 Combine like terms: -3 + 3 = 0 0 + 2X + -6x + 4xX = -10 + 3x + 3 + 4x2 2X + -6x + 4xX = -10 + 3x + 3 + 4x2 Reorder the terms: 2X + -6x + 4xX = -10 + 3 + 3x + 4x2 Combine like terms: -10 + 3 = -7 2X + -6x + 4xX = -7 + 3x + 4x2 Add '6x' to each side of the equation. 2X + -6x + 6x + 4xX = -7 + 3x + 6x + 4x2 Combine like terms: -6x + 6x = 0 2X + 0 + 4xX = -7 + 3x + 6x + 4x2 2X + 4xX = -7 + 3x + 6x + 4x2 Combine like terms: 3x + 6x = 9x 2X + 4xX = -7 + 9x + 4x2 Reorder the terms: 7 + 2X + -9x + 4xX + -4x2 = -7 + 9x + 4x2 + 7 + -9x + -4x2 Reorder the terms: 7 + 2X + -9x + 4xX + -4x2 = -7 + 7 + 9x + -9x + 4x2 + -4x2 Combine like terms: -7 + 7 = 0 7 + 2X + -9x + 4xX + -4x2 = 0 + 9x + -9x + 4x2 + -4x2 7 + 2X + -9x + 4xX + -4x2 = 9x + -9x + 4x2 + -4x2 Combine like terms: 9x + -9x = 0 7 + 2X + -9x + 4xX + -4x2 = 0 + 4x2 + -4x2 7 + 2X + -9x + 4xX + -4x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 7 + 2X + -9x + 4xX + -4x2 = 0 The solution to this equation could not be determined.
| b+8+6=18 | | 2x+10=x+94 | | x-5v=3 | | 101-3x=33x+21 | | 4b+b=20 | | 8-8x=53-29x | | 2(2x+7)+9=3+2x | | -3k+7k=-8 | | 5t-8=3t | | 6x-69=4x-13 | | 4(d+2)=30 | | n-7+6n=-21 | | 5t^2=6t | | 2*(3x+5)-5*(6x-6)=8*(10x-8) | | 6x+34=15x-65 | | 4x^2+4x=8 | | 5x^3+2x^2+20x+8=0 | | 45x^2+3x=0 | | 80-2x=25x+20 | | 3n^2-5n-8=0 | | 5x^2-30x+20=0 | | 2n-3=17+n | | 3-3m-5=-5 | | 6-9x=130-37x | | 2v+6-7v=11 | | 4m=52 | | -3r-5r=8 | | y=(-2xp)-4 | | 6+2n=4n+8 | | y=(-2x)-4 | | 3a-15=24 | | -4(a+4)+8a=-2(2+4a) |